An Exploration of Power Reflected in BTS “Love Myself” Campaign - Nur Aisyah; Andi Samsu Rijal; Dahniar Dahniar (English Literature Studi Program Universitas Islam Makassar, 2025)
This study examined how power is reflected in BTS’s Love Myself campaign, which have had significant emotional and social impact, especially among their fans, ARMY. Using Norman Fairclough’s three-dimensional model of discourse analysis, this study analyzed how RM’s speech at the UN in 2018 constructed power relations. The data set consists of six selected excerpts from the speech, supported by news articles and selected screenshots of fans’ social media posts. Findings showed that the data demonstrated different forms of horizontal power between BTS and audience: one symbolic, one persuasive, two normative, and the other two were a combination of all three. The active participation of ARMY further strengthens the campaign in the digital space. The results also showed that the campaign helped shift shame-oriented cultural norms toward a more open and accepting environment regarding insecurity, self-worth, and mental health.